МЕТОДОЛОГІЧНІ ПІДХОДИ ТА ПРИНЦИПИ НАУКОВОГО ДОСЛІДЖЕННЯ БІОФІЛЬНОГО ДИЗАЙНУ РЕАБІЛІТАЦІЙНИХ КОМПЛЕКСІВ В УМОВАХ СУЧАСНИХ СОЦІОКУЛЬТУРНИХ ТРАНСФОРМАЦІЙ - РИЖОВА, ІРИНА; ШВЕЦЬ, ОЛЕНА (Humanities Studies, 2025)
Relevance of the study. In modern conditions of increasing urbanization, technogenic load and social crises, the problem of creating environments focused on physical and psycho-emotional human recovery is of particular importance. Rehabilitation complexes as spaces of medical and social care play a key role in the processes of restoring health, adaptation and returning a person to active life. At the same time, traditional approaches to their design often focus mainly on functional and technological aspects, ignoring the deep psychological needs of users and their connection with the natural environment. The purpose of this study is a comprehensive scientific, theoretical and practical substantiation of the principles, approaches and methods of applying biophilic design in the architectural and spatial organization of rehabilitation complexes in order to form an effective medical and rehabilitation environment that contributes to the physical, psycho-emotional and social recovery of a person. Research methods. The study used the system-structural method, the expert assessment method, the modeling method, etc. The study of biophilic design in rehabilitation complexes requires the isolation of three main blocks: theoretical and methodological, analytical and practical and applied, each of which forms its own contribution to the overall process of building the concept. Biophilic design, based on the idea of a person's innate need to interact with nature, appears as a promising direction in the formation of a medical and rehabilitation environment. This problem is especially relevant in the conditions of modern Ukraine, where there is a growing need to create effective rehabilitation spaces for military and civilian personnel affected by military actions. The lack of unified principles and clearly formed approaches to the integration of biophilic design into rehabilitation complexes complicates the design process and reduces the potential of such environments as tools for comprehensive human recovery. In this context, the need to develop methodological foundations for the formation of principles and approaches to the study of biophilic design, which will take into account both spatial and artistic, psycho-emotional, functional and environmental aspects, is becoming more urgent. Such a scientific approach will allow not only to systematize existing knowledge, but also to create a theoretical basis for the practical implementation of biophilic solutions in rehabilitation complexes, contributing to improving the quality of the treatment environment and forming a humanistically oriented architecture of the future. Conclusion. The methodology of biophilic design research includes theoretical analysis, spatial analytics, modeling, empirical research, which allows for the formation of scientifically sound recommendations.